Biochemical features of the introduced population of Serratula coronata L. (Asteraceae) in Central Polissia of Ukraine - І. В. Іващенко; Д. Б. Рахметов; О. М. Вергун (Plant Varieties Studying and Protection)
Purpose. To establish the biochemical composition of the above ground part of Serratula coronata L. (Crowned saw-wort) for introduction in Central Polissia of Ukraine. Methods. The object of research was the plants of S. coronata from the collection of the Botanical garden of Zhytomyr National Agroecological University. Plant raw material was evaluated in the flowering phase in the biochemical laboratory of the Department of Cultural Flora of the M. M. Hryshko National Botanic Gardens of the National Academy of Sciences of Ukraine according to the relevant methods during 2014–2016. Results. The results of the study of phytochemical features of S. coronata under conditions of introduction in the Central Polissia of Ukraine in the flowering phase are given. Quantitative content of raw material in dry matter, total sugars, carotene, ascorbic acid, tannins, fats, free acids, macroelements of phosphorus, calcium and trace elements of iron, copper, zinc, manganese was revealed. Conclusions. The biochemical composition of the above ground part of S. coronata was determined for the first time in the conditions of introduction in Central Polissia of Ukraine. The peculiarities of the dependence of the content of biochemical compounds and macroelements on age characteristics of plants were determined. Plants of S. coronata of the third year of life were distinguished by the highest content of ascorbic acid, carotene and dry matter; two-year – organic acids, phosphorus, ash, common sugars; the fourth year of life – the content of oil and calcium. Significant amounts of vitamin C and iron were found in the raw material. The obtained results testify to the prospect of further study of the pharmacological properties of S. coronata in order to obtain new food products, bio-additives and phytopreparations enriched with biologically active substances and essential for human life.